(untitled) (African Journal of Biomedical Research, 2021)
The ingestion of smoked foods has been linked to the development of cancer. Polycyclic aromatic hydrocarbons have been recognized as carcinogenic compounds which contaminates smoked foods; their ingestion has been linked to the development of cancers such as breast cancer. Breast cancer may be evaluated using the nuclear bone scan as an imaging modality. This study reviewed bone scan results of patients with a positive history of consumption of smoked foods who presented at a Nuclear Medicine facility in South-West Nigeria. Our results show a significant association between a positive history of consumption of smoked foods and the presence of advanced breast cancer on the bone scan ((χ2 = 11.190, p = 0.001, df = 2; Crude Odds Ratio (95% CI) = 1.692(1.242-2.304). Thus, those patients with a history of eating smoked foods have between 50-100% increase in the risk of having abnormal scan findings. In a logistic regression, this association was retained (AOR=0.591 (0.434-0.805). Recommendations are made to address the significance of these findings.